Dendritic cell-based vaccination combined with gemcitabine increases survival in a murine pancreatic carcinoma model. Issue 9 (29th March 2007) - Bauer, C; Bauernfeind, F; Sterzik, A; Orban, M; Schnurr, M; Lehr, H A; Endres, S; Eigler, A; Dauer, M
Abstract : Background: Tumour-specific cytotoxic T lymphocytes (CTLs) can be activated in vivo by vaccination with dendritic cells (DCs). However, clinical responses to DC-based vaccination have only been observed in a minority of patients with solid cancer. Combination with other treatment modalities such as chemotherapy may overcome immunoresistance of cancer cells. It has been shown previously that gemcitabine sensitises human pancreatic carcinoma cells against CTL-mediated lysis. Here, a murine pancreatic carcinoma model was used to investigate whether combination with gemcitabine increases therapeutic efficacy of DC-based vaccination. Methods: Bone marrow-derived DCs from C57BL/6 mice were loaded with UV-irradiated, syngeneic Panc02 carcinoma cells and were administered subcutaneously. For prophylactic vaccination, mice were vaccinated three times at weekly intervals prior to tumour challenge with Panc02 cells. Therapeutic vaccination was started when tumours formed a palpable nodule. Gemcitabine was administered intraperitoneally twice weekly. Results: Prophylactic DC-based vaccination completely prevented subcutaneous and orthotopic tumour development and induced immunological memory as well as tumour antigen-specific CTLs. In the subcutaneous tumour model, therapeutic DC-based vaccination was equally effective as gemcitabine (14% vs 17% survival at day 58 after tumour challenge; controls, 0%). Combination of the two strategies significantly increased survival of tumour-bearing mice (50% at day 58 after tumour challenge). DC-based vaccination also prevented death from pulmonary metastatisation after intravenous injection of Panc02 cells. Conclusion: DC-based immunotherapy may not only be successfully combined with gemcitabine for the treatment of advanced pancreatic carcinoma, but may also be effective in preventing local recurrence or metastatisation in tumour-free patients.